Continuity in intuition and insight: from real to naturalistic virtual environment - M. Eskinazi (Nature Portfolio, 2021)
Abstract Intuition and insight can be deployed on the same continuum. Intuition is the unconscious ability to create links between information; insight is a process by which a sudden comprehension and resolution of a situation arises (i.e. euréka). In the present study, real and virtual environments were used to trigger intuition and insight. The study hypothesised that immersion in real primed environments would facilitate the emergence of intuition and insight in a virtual environment. Forty nine healthy participants were randomly assigned to two groups: “primed” and “non primed.” “Primed” participants were immersed in a real environment with olfactory and visual cues; “non primed” participants did not receive any cues. All participants were exposed to a 3D naturalistic virtual environment which represented a district in Paris via a Head Mounted Display (HMD). Locations presented in the virtual scene (i.e. café places) were related to both olfactory and visual primes (i.e. café) and were based on the continuity between real and virtual environments. Once immersed in the virtual environment, all participants were instructed to use their intuition to envision the selected locations during which Skin Conductance Responses (SCRs) and verbal declarations were recorded. When initiation (a) and immersion (b) phases in the virtual environment were considered, “primed” participants had higher SCRs during the immersion phase than the initiation phase in the virtual environment. They showed higher SRCs during the first part of the virtual immersion than “non primed” participants. During the phenomenological interview, “primed” participants reported a higher number of correct intuitive answers than “non primed” participants. Moreover, “primed” participants “with” insight had higher SCRs during real environment immersion than “primed” participants “without” insight. The findings are consistent with the idea that intuitive decisions in various tasks are based on the activation of pre-existing knowledge, which is unconsciously retrieved, but nevertheless can elicit an intuitive impression of coherence and can generate insight.